2022
DOI: 10.1177/10534512221081240
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Whole Number Addition and Subtraction to Students With Learning Disabilities

Abstract: Students with learning disabilities in mathematics often struggle with the underlying concepts of multidigit addition and subtraction. To help students build a conceptual understanding of these computations, teachers can utilize evidence-based practices such as the concrete, semi-concrete, abstract frameworks and the use of multiple, visual representations. This column presents five key strategies that incorporate evidence-based practices and teach whole number operations that rely on place value understanding. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Students with SEN had a significantly lower intercept value. This result is consistent with the findings that especially students with SEN-L often do not master the basic arithmetic operations taught in primary school even in secondary school (e.g., Peltenburg et al, 2012 ; Gebhardt et al, 2014 ; Rojo and Wakim, 2022 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Students with SEN had a significantly lower intercept value. This result is consistent with the findings that especially students with SEN-L often do not master the basic arithmetic operations taught in primary school even in secondary school (e.g., Peltenburg et al, 2012 ; Gebhardt et al, 2014 ; Rojo and Wakim, 2022 ).…”
Section: Discussionsupporting
confidence: 91%
“…Previous research has also shown that students with SEN have difficulty acquiring adequate computation skills ( Gersten et al, 2005 ; Evans, 2007 ; Bryant et al, 2008 ; Wei et al, 2013 ; Soares et al, 2018 ). For example, at the end of primary school, many students with SEN-L have acquired lower competencies in the development in mathemtics in general (e.g., Gebhardt et al, 2014 , 2015 ) and in the development of mental arithmetic computation for numbers up to 100 compared to their peers without SEN-L ( Peltenburg et al, 2012 ; Rojo and Wakim, 2022 ).…”
Section: Mental Addition and Subtraction And Its Differential Develop...mentioning
confidence: 99%
See 2 more Smart Citations